PP.46 What Influences a Parent's Decision-Making For Perinatal Autopsy? A Qualitative Investigation. (26th April 2013) - Meaney, S; Gallagher, S; Lutomski, JE; Donoghue, K O'
Abstract : Objectives: This study aims to gain insight into parents' perception of autopsy and the decision-making processes. Study design: A qualitative semi-structured interview format was utilised. Purposive sampling was used to recruit 10 parents who either consented or declined autopsy from a large hospital, where there were 30 stillbirths in 2011. Interpretative phenomenological analysis (IPA) was employed as the analytic strategy. IPA allows for close examination of parents' experiences using a small purposive sample by identifying superordinate themes which highlight what is important to the participant but also detail the meaning of these phenomena in a social context. Results: Findings revealed four superordinate themes influencing parents' decision-making; attribution of death, searching for meaning, knowledge of the autopsy procedure and protective parent. Parents discussed the need for the certainty of the diagnosis as it influenced emotional reactions including difficulty in coping with the uncertainty of the outcome of a future pregnancy. Parents, who declined autopsy, strongly indicated that the key reason was to protect their child from further harm. Parents' knowledge and understanding of the autopsy process was acquired primarily from public discourse, with particular reference to television programmes, which elicited negative responses from parents due to their perception of the invasive nature of the autopsy process. Conclusion: These findings have implications for psychological models of decision making and clinical practise. This study underscores the challenges that clinicians face in overcoming public misperceptions of the invasiveness of some autopsy procedures.